Sustainability performance analysis and decision-making for minerals beneficiation : a South African iron and steel scrap case study - Chitaka, Takunda Yeukai (Department of Chemical Engineering, 2016)
It is widely accepted that downstream mineral resource beneficiation has the potential to promote socio-economic growth in resource-rich nations. Many African countries, including South Africa, are thus prioritizing mineral beneficiation in their national policies and development strategies. However, policies with a strict focus on promoting downstream mineral beneficiation may come at the expense of other emerging sectors, as well as overshadow potential economic benefits of cross linkages into lateral sectors. Therefore, when presented with different beneficiation alternatives for a particular commodity, decision makers ideally need to base decisions on a systematic analysis of positive and negative impacts, if the sustainability benefits are to be maximised. Decision support frameworks (DSF) have been recommended for the promotion of sustainable development in the minerals sector, in particular for corporate and public policy development. They provide a structured and systematic approach to decision-making in complex situations, often characterised by multiple decision-makers with potentially conflicting views and objectives. Furthermore, the structured approach allows for transparent decisions to be made which take into consideration both the decision situation and stakeholder perspectives. Research thus far, on DSFs in the minerals sector, has been in the context of mineral processing decision situations which were primarily concerned with technology selection or process design. This dissertation investigates the applicability of decision support frameworks for sustainability performance analysis and comparison of decision alternatives, aimed at strategic planning in the minerals sector. More specifically, this entails the sustainability performance evaluation of decision alternatives as well as exploration of stakeholder perspectives regarding the relative importance of different factors in the decision-making process. The dissertation places particular emphasis on the different steps outlined in DSFs, rather than the final decision outcome, enabling analysis of the value that may be gleaned from the DSF as a whole, and from the individual stages. The application of decision support frameworks is demonstrated for the case of the iron and steel scrap industry in South Africa, with a particular focus on the potential for increased local beneficiation of scrap in steel mills and/or foundries. The export of scrap metal has been identified as a significant concern to some, as it is viewed to come at the expense of local beneficiation, hampering access to affordable and quality scrap for local processors. As such, decision-makers are faced with the question of which option for scrap metal processing has the most potential sustainability benefits. The sustainability performance evaluation was based on available industry data, and assumptions were made when data were unavailable. Interviews were conducted with key stakeholders in the industry, which included representatives of metal recycling, steel mills, foundries and institutions.